Lacustrine Ecosystems of the Steppe Dnipro Region: Typology, Ecological Status Assessment and Conservation Value - Manyuk, Vadym; Serdyuk, Svitlana; Dovganenko, Denis; Demirova, Siyka (Dr. Viktor Koval, 2025)
Introduction. Lacustrine ecosystems are crucial and irreplaceable in biodiversity conservation and provide specific ecosystem services. Although systematic long-term studies on the inventory and typology of lakes worldwide have been conducted, the issue remains poorly understood in the Steppe Dnipro region of Ukraine. Although lacustrine systems are vulnerable and characterised by significant diversity, this requires early environmental assessment and implementation of management plans to ensure their conservation. Aim and tasks. This study aimed to develop a typological scheme for open-type lake ecosystems in the Steppe Dnipro region with a set of typological criteria that can be combined to perform various applied environmental tasks, including the assessment of the ecological state of water bodies, inventory, environmental monitoring, and study of the dynamics of lake systems in the context of climate change. Results. The regional typological scheme was developed based on international and regional experience in the field of ecosystem classification (New Broad Typology for European Rivers and Lakes). The criteria are based on the generalisation of long-term studies of lake ecosystems in the region as components of the regional ecological network. In total, 53 criteria were identified, and a separate typological scheme with fewer criteria was developed for man-made reservoirs. The typology was adapted for use in GIS projects, where each criterion has a range of values. Tabular examples of the application of the typological scheme to identify typologically similar water bodies and for the rapid assessment of their ecological status are presented. Conclusions. The regional typological scheme allows for the distinction of water body types by various combinations of criteria. In practice, it is convenient to quickly create samples of lakes that are similar in certain respects for specific environmental or economic tasks. Further work with the scheme involves filling in the dataset, refining the parameters, and creating lake clusters using cluster analysis algorithms. After verification, the typological scheme can be transformed into a public web portal with the functions of an open database of data on lake-type reservoirs (with the possibility of updating and supplementing) and used to assess the ecological status and track current changes in the ecosystems of lakes and man-made reservoirs in the region.